Insights on Original Narrative Fiction in the Political of Diego de Saavedra, Fajardo, Andrés Mendo, and Francisco Garau - Bernat Vistarini, Antonio; Cull, John T. (Análisis. Revista de investigación filosófica, 2018)
This study explores the function of several types of narrative fiction utilized by three of the most distinguished political emblematists of the Hispanic Baroque: Diego Saavedra Fajardo, Andrés Mendo (who borrows liberally from the work of Solórzano Pereira) and the expressly anti-Machiavellian works of Francisco Garau. We consider the rationale behind choosing the emblem as a vehicle to express Counter-reformation political thought and we trace an evolution that leads to one of the books of Garau, which reveals itself to be a highly original work that propagates traditional rhetorical procedures and at the same time it conceals a radical skepticism affecting both the form and content of the work. Keywords: Emblems, Spanish Political Literature, Golden Age Literature, Narrative Fiction